Access Bank's Digital Transformation and Adoption of Communication Technologies for Internal Operations in the Post-COVID Era: A Managerial Perspective (Integral Research, 2025)
The study examined the Access Bank’s transformation and acceptance of Digital Communication Technologies for internal communication after the Covid-19 pandemic era. The theoretical framework for the study is Technology Acceptance Model (TAM). The qualitative approach was adopted using Key Informant Interview (KII) as the research method with interview guide as the instrument of data collection. For the KII, using purposive sampling technique, five persons in the managerial departments were interviewed to select only those who must have been working in Access Bank before the Covid-19 lockdown and for at least five years. Findings revealed that Access Bank’s compliance with Covid-19 pandemic work restrictions was high through partial lock during the pandemic period. Also, the use of digital communication technologies significantly increased to a great extent after Covid-19 and has permanently changed some works ethics, affected productivity, creativity and innovation in the bank with dominant media identified as Zoom, Skype and Microsoft Team for video conferencing and WhatsApp and Email for quick communication. It is recommended that the management of bank industry should train the staff on the use of advanced virtual communication platforms to maintain work ethics and information flow.
Keywords: Access Bank, Digital Communication Technologies, Internal Communication, Covid-19 Lockdown, Post Pandemic, Work From Home.